IMPLEMENTATION OF ONLINE TRIALS IN NARCOTICS CRIME NUMBER 112/PID.SUS/2022/PN.BNJ (CASE STUDY IN THE BINJAI STATE COURT) - Rizal Efendi Harahap; Yasmira Mandasari Saragih; Rahmayanti (PT. Radja Intercontinental Publishing, 2024)
The Covid-19 pandemic has forced the Indonesian Supreme Court to formulate formal juridical rules for online trials regarding social distancing. However, the legal basis and legal strength of decisions carried out online are still debatable, plus there are several obstacles and obstacles in their implementation. This research uses an empirical normative approach, namely direct research in the field (field resources) by exploiting materials.law.primary, namely Court Decisions, Interviews and Observations are also materials..secondary in the form of books, papers and journals. Next, it is analyzed by examining the data collected from the case study study and synchronizing it with the results of the study of statutory regulations.Online trial for registered narcotics criminal cases112/ Pid.Sus/2022/PN.Bnj is formally implemented based on PERMA RI No. 4 of 2020 jo. PERMA RI No. 8 of 2022, the implementation of which experienced several obstacles, specifically in the form of the video teleconference network (via zoom) being disconnected or disrupted. Then, inadequate supporting facilities such as hardware, internet network and electricity can go out at any time, disrupting the online trial process. It is hoped that the research can contribute ideas to practitioners and academics, especially to the legislature and judiciary so that improvements in the implementation of online trials in Indonesia can take place.